Community Participation Management On The Effectiveness Of "Rumah Kolong" School Management - Asriadi, Asriadi (MACCA : Science-Edu Journal, 2024)
This study aims to analyze community participation in the management of "rumah kolong" schools. Using descriptive qualitative research methods, this study examines the types of participation, the elements of the community involved and the impact of participation. The results show that community involvement is instrumental in supporting the infrastructure and learning in kolong schools, which are held under stilt houses as an alternative to education in remote areas. Community participation in the form of financial, labor and moral support has proven effective in creating a sustainable learning environment despite accessibility limitations. This research provides a practical contribution to the participatory management model of education in the 3T (Disadvantaged, Frontier and Outermost) areas